G90(P) N2o laughing matter. (27th April 2015) - Seddon, P; Noble, K
Abstract : Aims: To investigate the risks posed to young people from the recreational use of nitrous oxide ("laughing gas"). Methods: We highlight the case of a girl aged 15 who presented to a Children's Emergency Department with significant subcutaneous emphysema, pneumothorax and pneumomediastinum, following nitrous oxide inhalation at a festival the previous day. We reviewed the current literature in order to understand the scope of nitrous oxide use amongst the teenage population. We reviewed previous published case studies along with statistics from the International Centre for Drug Policy. 1 Results: Pneumothorax and pneumomediastinum are recognised complications of illicit drug use. The underlying pathophysiology relates to barotrauma created by the inhalation technique. 2 Inhalation of Nitrous Oxide has the added complication of pneumothorax expansion, due to its high blood-gas partition coefficient. Accordingly complications from the inhalation of nitrous oxide may be significantly worse than for users of other inhaled recreational drugs. Recreational nitrous oxide use amongst the teenage population has risen exponentially over the past five years, with 7.6% of 16–24 year olds in England and Wales admitting to having tried nitrous oxide in 2013. 3 Seventeen deaths in the UK were attributable to nitrous oxide between 2006–2012, 1 a figure which we would expect to rise given current surge in usage. Conclusion: Nitrous oxide inhalation poses a significant risk to the teenage population. Pneumothorax should be considered in any teenager presenting after inhaling gaseous or volatile agents, and recreational drug use should be considered and addressed in teenagers presenting with a pneumothorax of unknown aetiology. References: John Corkery HC, Loi B, Goodair C, Schifano F. Drug Related Deaths in the UK: Jan-Dec 2012–2013 Phillipe Camus ECR. Drug-induced and Iatrogenic Respiratory Disease: CRC Press; 2010. 364p Office H. Drug Misuse: Findings from the 2013/14 Crime Survey for England and Wales. www.gov.uk : Government, ONS; 2014 15/08/2014.